Assessment of neutralizing capacity of antibodies raised in mice against a Crotalus durissus terrificus phosphodiesterase - Alonso, María del Rosario (2019)
Fil: Alonso, María del Rosario. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.